Preparation method of boron nitride and aluminum nitride composite ceramic
Aluminum nitride is generated by the sol method, combined with ultrasonic dispersion treatment of modified boron nitride, and spray drying, cold isostatic pressing and other steps are used to solve the problem of uniform compounding and strength improvement of boron nitride aluminum nitride composite ceramics, achieving It improves the uniformity and density of the material and significantly improves the mechanical strength of the composite ceramics.
Patent Information
- Application Number
- CN202411559558.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The prior art is difficult to achieve uniform composite of boron nitride aluminum nitride composite ceramics, resulting in unstable material performance and insufficient in improving material strength.
Use isopropyl aluminum and aluminum salt as the starting raw material, generate aluminum nitride through the solution method, and use modified boron nitride for ultrasonic dispersing treatment. Then spray drying, cold and other static molding, pre -fired, high temperature nitrogen nitride And without pressure sintering and other steps, prepare boron nitride and aluminum -noning ceramics.
The uniformity and density of the material are improved, the mechanical strength of the composite ceramic is significantly improved, the process is simplified, and the production cost is reduced.
Smart Images

Figure CN119350041A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic composite material preparation, and specifically relates to a method for preparing boron nitride aluminum nitride composite ceramic. Background Art
[0002] Boron nitride aluminum nitride (BN / AlN) composite ceramics have broad application prospects in electronic packaging, high-temperature sensors, thermal management devices and other fields due to their excellent thermal conductivity, electrical insulation, chemical stability and mechanical properties. However, traditional preparation methods often make it difficult to achieve uniform compounding of BN and AlN, resulting in unstable material properties. At present, the methods for preparing BN / AlN composite ceramics mainly include pressureless sintering and hot pressing sintering. Although these methods can prepare composite ceramics with certain properties, they are insufficient in improving the strength of composite ceramics. Specifically, the pressureless sintering method is simple to operate, but it is difficult to control the uniform distribution of BN and AlN, and local enrichment is prone to occur, resulting in unstable material properties. In addition, the pressureless sintering method usually requires a higher sintering temperature, which not only increases energy consumption, but may also cause structural changes in the material at high temperatures, thereby affecting the performance of the final product. For example, during high-temperature sintering, larger pores may be formed inside the material, resulting in reduced density, which in turn affects thermal conductivity and mechanical properties. The hot pressing sintering method can effectively reduce the pores inside the material and improve the density by sintering at high temperature and high pressure. However, this method requires special hot pressing equipment, which increases production costs. In addition, the operation process of hot pressing sintering is relatively complicated, and the control requirements of process parameters are high, which makes it difficult to achieve large-scale production.
[0003] Researchers have tried many methods, such as introducing sintering aids and using chemical vapor deposition (CVD) treatment. Although these methods have improved the material properties to a certain extent, there are also some new problems, such as the introduction of impurities and complex processes. In particular, for the key issue of improving its strength, the existing technology has not yet found an effective solution. The strength of composite ceramics is one of the key factors that determine whether they can withstand complex working conditions. Therefore, developing a preparation method that can effectively improve the strength of composite ceramics has become a problem that needs to be solved urgently. Summary of the invention
[0004] The present invention aims at the problems existing in the prior art and provides a method for preparing a boron nitride aluminum nitride composite ceramic, which solves the problems existing in the prior art such as many pores, low density, poor uniformity, etc., and improves the mechanical strength of the composite ceramic. The whole process of the present invention is simple, and no additional sintering aid or complicated CVD treatment is required, and hot pressing sintering is not required, which greatly reduces the production cost and improves the preparation efficiency.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a boron nitride aluminum nitride composite ceramic comprises the following steps:
[0007] (1) dissolving aluminum isopropoxide in isopropanol, adding aluminum salt and citric acid aqueous solution, stirring for a certain period of time, and adjusting the pH value to 4-6 to obtain a sol;
[0008] (2) adding modified boron nitride to the sol prepared in step (1), and performing ultrasonic dispersion treatment to ensure that the modified boron nitride is evenly mixed in the sol;
[0009] (3) spray drying the uniformly mixed sol in step (2) to obtain a precursor powder;
[0010] (4) placing the precursor powder into a mold and performing cold isostatic pressing to obtain a cold pressed blank;
[0011] (5) placing the cold pressed blank in an inert atmosphere for pre-sintering at a temperature of 400 to 800°C;
[0012] (6) After the pre-sintering is completed, the green body is transferred to a reactor in an ammonia atmosphere for high-temperature nitridation reaction at a temperature of 1000-1200°C;
[0013] (7) After the high-temperature nitriding reaction is completed, the green body is placed in an inert atmosphere for pressureless sintering at a temperature of 1600-1850° C. to obtain a boron nitride aluminum nitride composite ceramic.
[0014] Furthermore, in the method, the molar ratio of aluminum isopropoxide, aluminum salt, and modified boron nitride is 1:0.3-0.5:4-6.
[0015] Furthermore, the aluminum salt is any one or more of aluminum nitrate, aluminum chloride, and aluminum sulfate, preferably aluminum nitrate.
[0016] Furthermore, in step (1), the mass volume ratio of aluminum isopropoxide to isopropanol is 1 g: 8 to 15 mL.
[0017] Furthermore, in step (1), after adding the aluminum salt, the mixture is stirred for 30 min to 1 h and then the citric acid aqueous solution is added.
[0018] Furthermore, the concentration of the citric acid aqueous solution in step (1) is 0.1 to 0.3 M, the amount of citric acid added is 0.1 to 0.3 times the molar amount of aluminum isopropoxide, and the mixture is stirred for 30 min to 1 h after the addition of the citric acid aqueous solution.
[0019] Furthermore, the preparation method of the modified boron nitride in step (2) is as follows:
[0020] (i) dissolving a silane coupling agent in water, stirring for 10 to 60 minutes, adding boron nitride powder, continuing to stir for 0.5 to 2 hours, filtering by suction, drying the filter cake, sieving, and obtaining boron nitride modified with a silane coupling agent for standby use;
[0021] The mass ratio of boron nitride powder to water is 1:6-15, and the mass of the silane coupling agent is 2-5% of the mass of the boron nitride powder;
[0022] (ii) dissolving ethanolamine in water at 60 to 90° C. at a mass ratio of 1:6 to 15 to obtain a solution 1;
[0023] (iii) adding 0.8 to 1 times the mass of ethanolamine into solution 1, and stirring for 15 to 24 hours, and then filtering and drying;
[0024] (iv) crushing and sieving the dried material to obtain the modified boron nitride;
[0025] Furthermore, the silane coupling agent is one or more of polydimethylsiloxane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, n-octyltriethoxysilane, triethoxyoctylsilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, and 3-glycidyloxypropyltrimethoxysilane.
[0026] Furthermore, the feed rate of the spray drying in step (3) is 10-20 mL / min, the air inlet temperature is 160-200° C., the air outlet temperature is 60-100° C., and the spray pressure is 0.05-0.1 MPa.
[0027] Furthermore, the pressure of the cold isostatic pressing in step (4) is 110 to 200 MPa.
[0028] Furthermore, the heating rate of the pre-sintering in step (5) is 4 to 6° C. / min, and the holding time is 2 to 3 h.
[0029] Furthermore, the heating rate of the high temperature nitridation reaction in step (6) is 4 to 6°C / min, and the insulation time is 2 to 3h.
[0030] Furthermore, the pressureless sintering time in step (7) is 2 to 4 hours.
[0031] The invention also provides boron nitride aluminum nitride composite ceramics prepared by the method.
[0032] The invention uses aluminum isopropoxide and aluminum salt as starting materials to generate aluminum nitride in situ, which is helpful for the uniform distribution of aluminum nitride phase in the final product, and improves the uniformity and density of the material. Aluminum isopropoxide and aluminum salt are used in combination as aluminum sources, mainly to provide enough aluminum elements in the preparation process, and to adjust the microstructure and final performance of the material through the synergistic effect of two different forms of aluminum sources. When aluminum isopropoxide and aluminum salt coexist, the interaction between them can promote the uniform dispersion of aluminum ions, prevent uneven precipitation caused by local supersaturation, thereby improving the uniformity and density of the final material.
[0033] The present invention uses citric acid as a catalyst. Citric acid can form a stable chelate with aluminum ions, thereby preventing the aluminum ions from precipitating too quickly during the hydrolysis process and ensuring uniform dispersion of the aluminum ions in the sol, thereby reducing the pores in the material and improving the density.
[0034] The modified boron nitride used in the present invention is first surface-modified by a silane coupling agent. Since the functional groups on the surface of boron nitride are very few and there are not enough hydroxyl or amino binding sites, the chemical activity of boron nitride is low. Therefore, the surface of boron nitride is chemically modified and surface coupling agent grafted by a silane coupling agent to enhance the group density on the surface of boron nitride, so that boron nitride has better dispersibility in the matrix and space for further reaction with other substances. After being modified by a silane coupling agent, it is reacted with ethanolamine, and the esterification reaction and intramolecular coordination (N|→B) between ethanolamine and the boron nitride containing hydroxyl groups on the surface are formed to form abundant>BO-H2C-H2C-H2N|→B< bond bridges between boron nitride sheets, which can form thermodynamically stable>BNB< covalent bonds during calcination, and the covalent bond has high bond energy, which can improve the thermal stability and strength of ceramics in macroscopic terms. Therefore, the modified boron nitride of the present invention can significantly improve the thermal stability and strength of ceramic materials.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The process is simple and does not require the introduction of additional sintering aids or complex CVD treatment.
[0037] 2. No need for hot pressing and sintering, which greatly reduces production costs and improves preparation efficiency.
[0038] 3. Improve the uniformity and density of the material and significantly improve the strength of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the SEM image of the cross section of the boron nitride aluminum nitride composite ceramic prepared in Example 1.
[0040] Figure 2The compressive and flexural strength test curves of the boron nitride aluminum nitride composite ceramic prepared in Example 1 are as follows: a) compressive strength; b) flexural strength.
[0041] Figure 3 The compressive and flexural strength test curves of the boron nitride aluminum nitride composite ceramic prepared in Comparative Example 1 are as follows: a) compressive strength; b) flexural strength.
[0042] Figure 4 The compressive and flexural strength test curves of the boron nitride aluminum nitride composite ceramic prepared in Comparative Example 2 are as follows: a) compressive strength; b) flexural strength.
[0043] Figure 5 The compressive and flexural strength test curves of the boron nitride aluminum nitride composite ceramic prepared in Comparative Example 3 are as follows: a) compressive strength; b) flexural strength. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It is worth noting that the methods used in the present invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercially available products unless otherwise specified, and their sources are not specifically limited.
[0045] Example 1
[0046] This embodiment provides a boron nitride aluminum nitride composite ceramic, and the preparation method thereof comprises the following steps:
[0047] (1) Dissolve 50 g of aluminum isopropoxide in 500 mL of isopropanol, add 20 g of aluminum nitrate, stir for 40 min, add 700 mL of 0.1 M citric acid aqueous solution, stir for 40 min, adjust the pH value to about 5, and obtain a sol;
[0048] (2) adding 30 g of modified boron nitride to the sol prepared in step (1), and performing ultrasonic dispersion treatment to ensure that the modified boron nitride is evenly mixed in the sol;
[0049] The preparation method of the modified boron nitride is as follows:
[0050] (i) dissolving polydimethylsiloxane in water, stirring for 30 min, adding boron nitride powder, continuing to stir for 1 h, filtering with suction, drying the filter cake in an oven at 70° C., and passing through a 100-mesh sieve to obtain boron nitride modified with a silane coupling agent for standby use;
[0051] The mass ratio of boron nitride powder to water is 1:10, and the mass of polydimethylsiloxane is 3% of the mass of boron nitride powder;
[0052] (ii) dissolving ethanolamine in 90° C. water at a mass ratio of 1:10 to obtain a solution 1;
[0053] (iii) adding boron nitride modified with a silane coupling agent in an amount equal to 1 time the mass of ethanolamine to solution 1, stirring for 20 hours, filtering with suction, and drying;
[0054] (iv) crushing the dried material and passing it through a 100-mesh sieve to obtain the modified boron nitride;
[0055] (3) spray drying the uniformly mixed sol in step (2) at a feed rate of 14 mL / min, an air inlet temperature of 180° C., an air outlet temperature of 80° C., and a spray pressure of 0.06 MPa to obtain a precursor powder;
[0056] (4) placing the precursor powder into a mold and performing cold isostatic pressing at 120 MPa to obtain a cold pressed blank;
[0057] (5) placing the cold pressed blank in an argon atmosphere, heating it to 650°C at a heating rate of 5°C / min for pre-sintering, and holding it for 2.5 h;
[0058] (6) After the pre-sintering is completed, the green body is transferred to a reactor in an ammonia atmosphere and heated to 1100°C at a heating rate of 5°C / min for high-temperature nitridation reaction, and the holding time is 2h;
[0059] (7) After the high-temperature nitriding reaction is completed, the green body is placed in an argon atmosphere for pressureless sintering at a temperature of 1700° C. for 3 h to obtain a boron nitride aluminum nitride composite ceramic.
[0060] The cross-sectional SEM image of the boron nitride aluminum nitride composite ceramic prepared in Example 1 is as follows: Figure 1 As shown in the figure, it can be seen that the flaky boron nitride and aluminum nitride particles are evenly distributed inside the material, without obvious aggregation or segregation; they present regular shapes, indicating that good crystallization effects have been obtained during the preparation process; the two are crisscrossed to build a stable network structure. This unique microstructure significantly improves the mechanical properties of the material.
[0061] Comparative Example 1
[0062] This comparative example provides a boron nitride aluminum nitride composite ceramic, which is different from Example 1 in that the boron nitride powder used is not modified with a silane coupling agent and ethanolamine, and the remaining steps are the same as those of Example 1.
[0063] Comparative Example 2
[0064] This comparative example provides a boron nitride aluminum nitride composite ceramic, which differs from Example 1 in that citric acid is replaced by hydrochloric acid, and the remaining steps are the same as those of Example 1.
[0065] Comparative Example 3
[0066] This comparative example provides a boron nitride aluminum nitride composite ceramic, which is different from Example 1 in that the preparation method of the modified boron nitride is as follows:
[0067] (i) dissolving ethanolamine in 90° C. water at a mass ratio of 1:10 to obtain a solution 1;
[0068] (ii) adding boron nitride powder of 1 times the mass of ethanolamine to solution 1, stirring for 20 hours, filtering and drying;
[0069] (iii) crushing the dried material and passing it through a 100-mesh sieve to obtain the modified boron nitride;
[0070] The remaining steps are the same as those in Example 1.
[0071] Performance Testing
[0072] The compressive strength and flexural strength of the boron nitride aluminum nitride composite ceramics prepared in Example 1 and Comparative Examples 1-3 were tested. The compressive strength was tested according to GB / T 8489-2006, and the flexural strength was tested according to GB / T 6569-2006. The test samples were prepared according to the corresponding national standards, and the sample test curves were as follows: Figure 2-5 As shown, the flexural strength and compressive strength of the samples were calculated according to the method specified in the national standard, and the results are shown in Table 1.
[0073] Table 1:
[0074]
[0075]
[0076] It can be seen from the test results of Example 1 and Comparative Examples 1-3 that the composite ceramic prepared by Example 1 through the optimization process has higher mechanical strength. Comparative Example 1 uses unmodified boron nitride, which, on the one hand, causes the boron nitride to be unable to be well mixed in the sol, resulting in agglomeration of the powder; on the other hand, it makes it impossible to form a good >BNB< covalent bond between the boron nitride sheets, which ultimately leads to a decrease in the strength of the ceramic. Comparative Example 2 uses hydrochloric acid as a catalyst. Hydrochloric acid does not have a chelating effect similar to citric acid, and cannot effectively promote the uniform dispersion of aluminum ions. Aluminum ions are prone to precipitate too quickly during the hydrolysis process, resulting in more pores inside the material and reduced density. Comparative Example 3 uses boron nitride that has not been surface-modified with a silane coupling agent, so that its surface lacks active groups and is easily agglomerated in the sol, and the interfacial bonding force with other components in the sol (such as aluminum salts, citric acid, etc.) is weak, resulting in unevenness inside the material, increased porosity, and decreased mechanical properties; in addition, weak interfacial bonding force will lead to the formation of defects at the interface, which will become the origin point of cracks, thereby reducing the flexural strength and compressive strength of the material. During the high-temperature sintering process, areas with weak interfacial bonding force will also be prone to peeling, further reducing the mechanical properties of the material.
[0077] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a boron nitride-aluminum nitride composite ceramic, comprising the following steps: (1) dissolving aluminum isopropoxide in isopropanol, adding aluminum salt and citric acid aqueous solution, stirring for a certain period of time, and adjusting the pH value to 4-6 to obtain a sol; (2) adding modified boron nitride to the sol prepared in step (1), and performing ultrasonic dispersion treatment to ensure that the modified boron nitride is evenly mixed in the sol; (3) spray drying the uniformly mixed sol in step (2) to obtain a precursor powder; (4) placing the precursor powder into a mold and performing cold isostatic pressing to obtain a cold pressed blank; (5) placing the cold pressed blank in an inert atmosphere for pre-sintering at a temperature of 400 to 800°C; (6) After the pre-sintering is completed, the green body is transferred to a reactor in an ammonia atmosphere for high-temperature nitridation reaction at a temperature of 1000-1200°C; (7) After the high-temperature nitriding reaction is completed, the green body is placed in an inert atmosphere for pressureless sintering at a temperature of 1600-1850° C. to obtain a boron nitride aluminum nitride composite ceramic.
2. The preparation method according to claim 1, characterized in that: In the method, the molar ratio of aluminum isopropoxide, aluminum salt and modified boron nitride is 1:0.3-0.5:4-6; the aluminum salt is preferably any one or more of aluminum nitrate, aluminum chloride and aluminum sulfate, and aluminum nitrate is more preferred.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass volume ratio of aluminum isopropoxide to isopropanol is 1 g:8-15 mL. After adding the aluminum salt, the mixture is stirred for 30 min-1 h and then the citric acid aqueous solution is added.
4. The preparation method according to claim 1, characterized in that: The concentration of the citric acid aqueous solution in step (1) is 0.1-0.3 M, the amount of citric acid added is 0.1-0.3 times the molar amount of aluminum isopropoxide, and the mixture is stirred for 30 min-1 h after the citric acid aqueous solution is added.
5. The preparation method according to claim 1, characterized in that: The preparation method of the modified boron nitride in step (2) is as follows: (i) dissolving a silane coupling agent in water, stirring for 10 to 60 minutes, adding boron nitride powder, continuing to stir for 0.5 to 2 hours, filtering by suction, drying the filter cake, sieving, and obtaining boron nitride modified with a silane coupling agent for standby use; The mass ratio of boron nitride powder to water is 1:6-15, and the mass of the silane coupling agent is 2-5% of the mass of the boron nitride powder; (ii) dissolving ethanolamine in water at 60 to 90° C. at a mass ratio of 1:6 to 15 to obtain a solution 1; (iii) adding 0.8 to 1 times the mass of ethanolamine into solution 1, and stirring for 15 to 24 hours, and then filtering and drying; (iv) crushing and sieving the dried material to obtain the modified boron nitride.
6. The preparation method according to claim 5, characterized in that: The silane coupling agent is one or more of polydimethylsiloxane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, n-octyltriethoxysilane, triethoxyoctylsilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, and 3-glycidyloxypropyltrimethoxysilane.
7. The preparation method according to claim 1, characterized in that: The feed rate of the spray drying in step (3) is 10-20 mL / min, the air inlet temperature is 160-200° C., the air outlet temperature is 60-100° C., and the spray pressure is 0.05-0.1 MPa.
8. The preparation method according to claim 1, characterized in that: The heating rate of the pre-sintering in step (5) is 4-6°C / min, and the holding time is 2-3h.
9. The preparation method according to claim 1, characterized in that: The heating rate of the high-temperature nitriding reaction in step (6) is 4 to 6°C / min, the holding time is 2 to 3 hours, and the time of the pressureless sintering in step (7) is 2 to 4 hours.
10. Boron nitride aluminum nitride composite ceramic prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of aluminum nitride / boron nitride composite ceramic powder
CN104725049A
Preparation method of high-density boron nitride self-lubricating composite ceramic
CN113149661A
Cubic boron nitride phase change enhanced aluminum nitride / boron nitride composite ceramic and preparation method thereof
CN114874019A
Aluminum nitride-boron nitride composite powder and method for producing the same
JP2008001536A
Method for preparing high-density hexagonal boron nitride ceramic material
US20160304346A1